Immunohistochemical detection of p53, PTEN, Rb, and p16 in canine osteosarcoma using tissue microarray. (July 2018) - Russell, Duncan S.; Jaworski, Lauren; Kisseberth, William C.
Although inactivating mutations of tumor suppressor genes are well described in cell lines of canine osteosarcoma (OS), expression of tumor suppressor proteins in spontaneous disease is poorly characterized. We determined the immunohistochemical expression of p53, PTEN, Rb, and p16 in a large cohort of dogs with OS. Formalin-fixed, paraffin-embedded samples of canine OS were analyzed retrospectively. Primary tumor samples from 145 dogs, collected between 2003 and 2008, were evaluated by tissue microarray. Streptavidin–biotin complex immunohistochemistry was performed using monoclonal antibodies for Rb and PTEN and polyclonal antibodies for p16 and p53. The average age of dogs was 7.6 y, and 118 of 145 (81%) were purebred. Most commonly represented purebreds were Greyhound (23%), Rottweiler (11%), and Labrador Retriever (10%). Immunohistochemical detection of p53, PTEN, Rb, and p16 was 81%, 61%, 66%, and 66%, respectively. The staining pattern for p16 was primarily cytoplasmic; the predominant pattern for PTEN, Rb, and p53 was cytoplasmic and nuclear. Exclusively cytoplasmic staining was noted in 19% of samples positive for p53 and 8% of samples positive for Rb. Kaplan–Meier curves showed that protein expression was not associated with significant differences in overall survival ( p > 0.191). We documented heterogeneity in both immunostaining and subcellular localization of tumor suppressor proteins, providing further characterization of canine OS.